Preparation of a Natural Candy from Date (Phoenix dactylifera L.), Olive (Olea europaea L.), and Carob (Ceratonia siliqua L.) Fruits - Abdellaoui Radia; Aissa Boukhiar; Khenchla Kechadi; Salem Benamara (Journal of Food Quality)
Until the early 1960s, the traditional recipe “Arkouy” from the mixture of carob (Ceratonia siliqua L.) powder and olive (Olea europaea L.) oil represented a sought-after food product in some localities of the Kabylian region (Northeastern Algeria). The present work attempted to improve this traditional recipe to obtain a natural candy from date (Phoenix dactylifera L.), olive (Olea europaea L.), and carob (Ceratonia siliqua L.) fruits. For this, different formulations with various proportions of the date paste, olive paste, and carob powder were obtained using a constrained mixture design (proportion of date paste ≥ 0.7). The hardness and total color difference in the CIELab system were adopted as dependent variables. For comparison purpose, the local commercial candy “Caprice” was taken as reference. In addition, the two formulations containing the three basic ingredients were analyzed for the overall acceptability, reducing power, and thermal analysis. At first approximation, it can be said that the formulation containing 75% date paste, 20% carob powder, and 5% olive paste ensures a balance between the target values of texture and color. The obtained candy can be used as a dietary supplement for all categories of consumers, especially patients with swallowing difficulties.